A Characterization of Ultrasonic Full Angle Spatial Compounding as a Possible Alternative for Breast Cancer Screening - MEDINA, Luis; CAMACHO, Jorge; FRITSCH, Carlos (Archives of Acoustics, 2015)
Breast cancer screening is based on X-ray mammography, while ultrasound is considered a complementary technique with improved detection in dense tissue. However, breast cancer screening requires a technique that provides repeatable results at the inspection interval which cannot be achieved with manual breast exploration.During the last years there have appeared several approaches to overcome this limitation by means of automated ultrasonic tomography performed with motorized probes or with a large set of array transducers.This work addresses these problems by considering a quite simple and low-cost arrangement, formed with a ring of conventional medical-grade array probes which are multiplexed to the electronics to build Full Angle Spatially Compounded (FASC) images. The work analyzes the performance of such arrangement in terms of resolution and isotropy, showing by numerical modelling and experimentally that it provides high resolution and homogeneity in the whole imaged region.The implementation of this technique would provide more than one circular FASC per second and a whole breast volume image in 1–2 minutes with conventional technology, a process fast enough to be clinically useful. Moreover, the automated technique is repeatable and can be used by the clinician to perform immediately the diagnosis without requiring additional data processing.